Numerical investigation of a liquid displacing a gas in thin porous layers. Issue 1 (21st October 2015) - Neumann, Tim; Boettcher, Konrad; Ehrhard, Peter
Abstract: This article deals with a liquid displacing a gas in a thin heterogeneous porous material, which occurs e.g. during the filling process of a lithium‐ion battery with an electrolyte. The investigation is based upon the local volume‐averaged Navier‐Stokes equations, using a Volume‐of‐Fluid method to treat the interface. For the flow the wall effect and capillary forces have to be considered. Capillary rise experiments are used to determine the permeability. Since the layers are thin and the characteristic size of the particles is comparatively large, friction with the electrode is taken into account with respect to the mobility of the contact line. The implemented models are validated against analytical results, showing a good agreement. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)